Tříválcové motory pro malé osobní automobily - Nárovec, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Cílem bakalářské práce je soustředit informace o tříválcových spalovacích motorech, užívaných v současné době v malých osobních automobilech. Práce je koncipována jako rešerše dostupných elektronických zdrojů, firemní literatury a článků z odborných periodik a uvádí základní technicko-ekonomické parametry 15 vybraných typů tříválcových motorů. Zahrnuje porovnání tříválcových zážehových motorů metodou rozhodovací analýzy a prognózu budoucího vývoje a uplatnění tohoto konceptu pohonných jednotek u malých osobních automobilů.

The aim of this bachelor’s thesis is to gather information about three-cylinder combustion engines used in small passenger cars nowadays. The thesis is conceived as a search of available electronic sources, company literature and specialized journal articles and involves fundamental technical-economic parameters of 15 selected types of three-cylinder engines. It contains the comparison of three-cylinder gasoline engines using the method of decision analysis and the prognosis of future development and application of such engine unit concept in small passenger cars.
Three-cylinder engines for small passenger cars
Keywords: malé osobní automobily; spalovací motory; tříválcové motory; downsizing; small passenger cars; combustion engines; three-cylinder engines; downsizing